Examining the Relationship Between Teacher Professional Learning Communities and Student Self-Regulated Learning: A Multilevel Structural Equation Modeling Approach - Vika Fransisca (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This study examines the gap between the recognized urgency of developing student self-regulated learning (SRL) and insufficient classroom implementation, often due to limited structured teacher collaboration. The research aims to analyze the multilevel relationship between teacher engagement in Professional Learning Communities (PLCs) and student SRL, mediated by SRL-supportive instructional practices and moderated by individual student characteristics and school organizational climate. A quantitative cross-sectional correlational design with stratified random sampling was conducted across 45 urban–suburban schools, involving 2,100 students (grades 4–11) and 280 teachers. Instruments included the Professional Learning Community Assessment-Revised (PLCA-R), the Self-Regulation Rating Scale (SRRS), and a 25-item teacher instructional practices inventory measuring explicit SRL strategy instruction, metacognitive modeling, contingent process-based feedback, and autonomy support. Data were analyzed using Multilevel Structural Equation Modeling (Mplus 8.0) employing robust maximum likelihood estimation. Results show significant direct effects of teacher PLC participation on student SRL, with meaningful mediation via SRL-focused instructional practices, and strong cross-level amplification from supportive school climates. Findings confirm that targeted, high-fidelity PLC engagement supports students’ metacognitive and motivational self-regulation when reinforced by enabling organizational conditions.